Skill acquisition and self-employment in Malaysia: A sufficient condition? - Isidore Ekpe; Razli Che Razak; Mohammad Ismail; Zulhamri Abdullah (2015)
The objective of this study is to examine the effect of skill training on self-employment practice among Malaysian University Graduates, as a means of assessing the success of several entrepreneurship development programs of the government. Studies have shown that skill acquisition is the most critical factor in the utilization of entrepreneurship opportunity for self-employment. However, vital as it may be, is skill acquisition a sufficient condition or factor for self-employment practice among Malaysian youths? Without other factors such as micro-credit, savings and social capital, can the skill-trained youths venture into self-employment? This is the focus of this study. The study adopts a quantitative survey by use of questionnaire and a proportionate stratified random sampling method to collect data. The study adopts data analysis using regression method. The study proffers solutions to the Malaysian Government for policy decisions that would engender greater participation of graduates in self-employment practice.